If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3a + -2cd) + -1(2b + 3cd) = 0 Remove parenthesis around (3a + -2cd) 3a + -2cd + -1(2b + 3cd) = 0 3a + -2cd + (2b * -1 + 3cd * -1) = 0 3a + -2cd + (-2b + -3cd) = 0 Reorder the terms: 3a + -2b + -2cd + -3cd = 0 Combine like terms: -2cd + -3cd = -5cd 3a + -2b + -5cd = 0 Solving 3a + -2b + -5cd = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '2b' to each side of the equation. 3a + -2b + 2b + -5cd = 0 + 2b Combine like terms: -2b + 2b = 0 3a + 0 + -5cd = 0 + 2b 3a + -5cd = 0 + 2b Remove the zero: 3a + -5cd = 2b Add '5cd' to each side of the equation. 3a + -5cd + 5cd = 2b + 5cd Combine like terms: -5cd + 5cd = 0 3a + 0 = 2b + 5cd 3a = 2b + 5cd Divide each side by '3'. a = 0.6666666667b + 1.666666667cd Simplifying a = 0.6666666667b + 1.666666667cd
| 5G+21=11g | | 0.06x+0.03y=27 | | 0.06x+0.03y=277 | | log(x^3-11x)-logx=2 | | 2y=4y-6 | | Y=-16x+80x | | (a^3-2a^3)-(3a^2-4a^3)=equation | | 25x-1=625 | | -3x-5(5x+13)=78 | | 4y-1=25 | | 2x+2=-1x+26 | | ((m^6n)^-2(m^2n^-2)^3)/m^-1n^-2 | | 9x+4=-18 | | 2/4p=3/4p+2 | | 15/17-2/34 | | 40=6x+16 | | R(4)+8= | | 10=6x+16 | | 15x+20x=1800 | | 1.8+32=90 | | -8y+8=37x-7 | | -3(5x+-4)=21 | | (-7p/2)=(-7/8) | | 13x^2+21=-5x^2+22 | | (-7p/2)(-7/8) | | 32x=1 | | (2-7x)+(2x+1)= | | 2-4x=4x+10 | | 5-2n=5 | | 4x+9=34x | | 4x=2x+2+3x-3 | | 0=6(x+2)(x-1) |